2013
DOI: 10.1002/app.40271
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of extruded nanocomposite based on polycarbonate/butadiene‐acrylonitrile‐styrene blend filled with multiwalled carbon nanotubes

Abstract: Nanocomposites of polycarbonate/acrylonitrile‐butadiene‐styrene (PC/ABS) with multiwall carbon nanotubes (MWCNT) prepared by masterbatch dilution are investigated in this work. Melt compounding with twin screw extruder is followed by complete characterization of morphology, rheological‐, mechanical‐, and thermal‐properties of the nanocomposites. Light‐transmission‐ and scanning electron microscopy shows the preferential location of MWCNT in the PC. Nevertheless, relatively good dispersion in the whole matrix i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Thereafter, this value decreased, which can be attributed to the aggregation of GNP particles. Recently, Marcin et al have also reported the 30% improvement in Young's modulus of PC/ABS blends reinforced by multi‐walled carbon nanotubes (MWCNT). Nevertheless, the nanocomposites ductility was reduced by MWCNT incorporation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, this value decreased, which can be attributed to the aggregation of GNP particles. Recently, Marcin et al have also reported the 30% improvement in Young's modulus of PC/ABS blends reinforced by multi‐walled carbon nanotubes (MWCNT). Nevertheless, the nanocomposites ductility was reduced by MWCNT incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…This temperature increased from 431 to 444 C for ABS with 3 wt% GNPs content and improved by 17 C for PC with the same GNP content. However, the study on PC/ABS/MWCNT nanocomposites showed a slight increase of DTG temperature for ABS and no significant change was observed for PC after the incorporation of carbon nanotubes [48].…”
Section: Thermogravimetric Analysismentioning
confidence: 96%
“…The dilution of pre-dispersed master batches on twin-screw extruder resulted in the improvement of thermal, mechanical and electrical properties of the PC/ABS blend. A balance between the mechanical and electrical properties observed during this research creates an attractive opportunity for the automotive and electronic industries (63).…”
Section: Polyblend Nanocomposites 649mentioning
confidence: 99%
“…Therefore, rheological properties are an effective means for predicting the dispersion of a nanofiller in polymers. [21][22][23] The G'-G" plot depending on GO insertion methods is shown in Figure 4(a) and complex viscosity is presented in Figure 4(b). Compared to the other composites, the PC-GO/ABS/ABS-g-MA composite showed a G'-G" pattern close to PC, suggesting that the GO was well distributed.…”
Section: 폴리머 제41권 제3호 2017년mentioning
confidence: 99%